The Influence of Taxpayer Awareness and Tax Sanctions on Taxpayer Reporting Compliance - Said Khaerul Wasif; Bayu Pratama; Indri Andini; Dian Hartanti (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2024)
This research aims to find out how taxpayers are aware of the reporting compliance of taxpayers registered with KPP Pratama Jakarta Cakung, as well as knowing the effect of tax sanctions on taxpayer reporting compliance. This research uses quantitative descriptive methods and data collection techniques through interviews, observation and documentation. The data used is the reporting compliance of taxpayers registered with KPP Pratama Jakarta Cakung. The analytical data used in this research is taxpayer awareness and tax sanctions. The results of this research are that taxpayer awareness has a positive effect, while tax sanctions have no effect on taxpayer reporting compliance.